Analysis of the Spread and Art Form of Spherical Censer from the Tang Dynasty to the Foreign Regions (Journal of Fiber Bioengineering and Informatics, 2022)
The spherical censer produced in the Tang Dynasty have standardized and identifiable art forms. Based on the study of their worldwide cover area, the actual impact of the Tang Dynasty arts and crafts on the development of world art can be specifically analyzed from the microscopic perspective, so as to further enrich the cultural and artistic academic value of the Silk Road. Based on the study of the origin and spread of spherical censer in the Tang Dynasty, this paper further analyzes the art form of spherical censer in foreign regions, by comparing physical form and decorative style, the relationship between the Silk Road and Tang arts and crafts has been analyzed, and the corresponding design principles of creations.